Risk analysis assessment of the influence of geological factors on exploration and mining investment alternatives : development of a microcomputer simulation model - Mallinson, Clyde A (Rhodes University, Faculty of Science, Department of Geology, 1987)
A microcomputer risk analysis model is developed and used in an exploration - delineation simulation to analyse in particular the effects of geological factors on exploration mining investment alternatives. Analysis of results indicate that geological parameters can have profound effects on such investment alternatives and that the role of the geologist in determining and evaluating the significance of the various geological factors is critical. Simulation examples highlight some of the key geological parameters and show how changes in these parameters influence both the expected mean results and the standard deviations of such means. The risk analysis model provides an ideal means of conveying the importance of the different geoiogical factors on exploration - delineation - mining investment alternatives and may be used as a geological education aid
Keywords: Geology, Economic; Risk assessment -- Computer simulation; Mineral industries -- Economic aspects -- Computer simulation; Prospecting -- Computer simulation